Prosedur Pengelolaan Arsip Dalam Peningkatan Efektivitas dan Efisiensi Kerja Studi Kasus Pada PT. Griya Asri Mandiri - Maghfirotin Munawaroh; Winarto Winarto; Nik Haryanti (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2023)
Archives are a collection of documents that are stored systematically so that anything needed can be found quickly and accurately (Gie, 1996:118). Every work and activity of government and private offices requires data and information. One source of information that must be owned by an office is archives. Therefore good archive management is needed. Organizing records properly and correctly will facilitate retrieval, so that when records are needed in making a decision, they can be found immediately. The problem in this research is how to manage archives at the office of PT. Griya Asri Mandiri and what are the obstacles experienced when managing records at the PT. Griya Asri Mandiri. The purpose of this research is to find out how the procedures for managing records at the office of PT. Griya Asri Mandiri and to find out what are the obstacles experienced when managing records at the office of PT. Griya Asri Mandiri. This research is a descriptive research with a qualitative approach. Data collection techniques used are observation, interviews and documentation. The results of this study indicate that in general archive management at the PT. Griya Asri Mandiri, among others: 1) Arrangement of archives 2) Storage of archives 3) Borrowing of archives 4) Retrieval of archives 5) Maintenance of archives 6) Security of archives 7) and shrinkage of archives. The obstacles faced when managing records include: 1) Human resources managing records. 2) Limited filing facilities.